2006
DOI: 10.1110/ps.062109706
|View full text |Cite
|
Sign up to set email alerts
|

A limited universe of membrane protein families and folds

Abstract: One of the goals of structural genomics is to obtain a structural representative of almost every fold in nature. A recent estimate suggests that 70%-80% of soluble protein domains identified in the first 1000 genome sequences should be covered by about 25,000 structures-a reasonably achievable goal. As no current estimates exist for the number of membrane protein families, however, it is not possible to know whether family coverage is a realistic goal for membrane proteins. Here we find that virtually all poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 65 publications
(89 reference statements)
1
70
0
5
Order By: Relevance
“…To make good use of dispersion forces and polar interactions, membrane proteins therefore may need to pack a larger fraction of their surface area to maintain a stable structure. Regardless of the reason for additional packing, this physical constraint seems to be important for disease etiology and could be a factor in the smaller number of integral-membrane protein families that seem to exist compared with water-soluble protein families (21,22). It has been suggested that water-soluble proteins evolved from the extramembrane segments of primordial membrane proteins (23).…”
Section: Resultsmentioning
confidence: 99%
“…To make good use of dispersion forces and polar interactions, membrane proteins therefore may need to pack a larger fraction of their surface area to maintain a stable structure. Regardless of the reason for additional packing, this physical constraint seems to be important for disease etiology and could be a factor in the smaller number of integral-membrane protein families that seem to exist compared with water-soluble protein families (21,22). It has been suggested that water-soluble proteins evolved from the extramembrane segments of primordial membrane proteins (23).…”
Section: Resultsmentioning
confidence: 99%
“…Although this coverage may seem limiting, results from the Protein Structure Initiative suggest that Ϸ90% of this unannotated space is comprised of variants of already discovered fold families (20), and that only 10% of the undiscovered fold families will actually be metalbinding (21). It appears that membrane proteins are similarly distributed, with the most abundant membrane folds being already described (22). Essentially, it seems unlikely that a new protein fold family will be discovered that is abundant enough to overly skew the observed results.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the effect these mutations might have on the folded structure and to provide evidence that the deduced structure of Sod2 TM IV is valid, we constructed a homology model of the membrane domain of Sod2. Mounting evidence suggests that a finite number of folds exist for membrane transporters (63) and that proteins with quite different primary amino acid sequences can have surprisingly similar structures. For example, the bile acid sodium symporter of Neisseria meningitides has a low primary sequence identity to E. coli NhaA, but the structure is surprisingly similar to that of NhaA (59).…”
mentioning
confidence: 99%